Asymmetries, Courts, and Comparative Constitutional Law : A Dynamic Accommodation of Diversity in Divided Multi-Tiered Systems - Bonifati, Lidia (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2026)
This book explores constitutional asymmetries in divided multi-tiered systems as a dynamic constitutional model to accommodate ethnocultural diversity through a comparative analysis of 12 constitutional systems from both the Global North and the Global South. It offers a unique integrated analysis of asymmetries as designed by the constitutional orders and interpreted by courts. The book contributes to the comparative constitutional scholarship on asymmetric federalism, providing for not only a qualitative but also a quantitative assessment of asymmetries. It combines traditional doctrinal and case-law analysis with emerging methodological approaches to legal research, such as empirical legal studies and decolonial comparative law.